2016
DOI: 10.1002/jcb.25797
|View full text |Cite
|
Sign up to set email alerts
|

7‐Dehydrocholesterol (7‐DHC), But Not Cholesterol, Causes Suppression of Canonical TGF‐β Signaling and Is Likely Involved in the Development of Atherosclerotic Cardiovascular Disease (ASCVD)

Abstract: For several decades, cholesterol has been thought to cause ASCVD. Limiting dietary cholesterol intake has been recommended to reduce the risk of the disease. However, several recent epidemiological studies do not support a relationship between dietary cholesterol and/or blood cholesterol and ASCVD. Consequently, the role of cholesterol in atherogenesis is now uncertain. Much evidence indicates that TGF-β, an anti-inflammatory cytokine, protects against ASCVD and that suppression of canonical TGF-β signaling (S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 74 publications
1
9
0
Order By: Relevance
“…Internalisation of TGF-β receptors through lipid-raft/caveolae-mediated endocytosis is more likely to facilitate receptor degradation through lysomal/proteasomal degradation pathways, thereby turning off TGF-β signalling. In line with this finding, we observed that triterpenoids and cholesterol derivatives suppress TGF-β responsiveness in cultured cells by causing the accumulation of cell-surface-bound TGF-β–TGF-β receptor complexes in the lipid rafts/caveolae of the plasma membrane, thereby facilitating the rapid degradation of these complexes, and thus attenuating TGF-β-stimulated signalling and -related responses 13–15 . The data obtained in this study reveal that PBrP suppresses the TGF-β signalling pathway, as determined using a 3TP-Lux plasmid [construct operated by the plasminogen activator inhibitor-1 (PAI-1) promotor] in a luciferase assay and observing Smad2/3 phosphorylation and their subsequent nuclear translocation.…”
Section: Introductionsupporting
confidence: 76%
“…Internalisation of TGF-β receptors through lipid-raft/caveolae-mediated endocytosis is more likely to facilitate receptor degradation through lysomal/proteasomal degradation pathways, thereby turning off TGF-β signalling. In line with this finding, we observed that triterpenoids and cholesterol derivatives suppress TGF-β responsiveness in cultured cells by causing the accumulation of cell-surface-bound TGF-β–TGF-β receptor complexes in the lipid rafts/caveolae of the plasma membrane, thereby facilitating the rapid degradation of these complexes, and thus attenuating TGF-β-stimulated signalling and -related responses 13–15 . The data obtained in this study reveal that PBrP suppresses the TGF-β signalling pathway, as determined using a 3TP-Lux plasmid [construct operated by the plasminogen activator inhibitor-1 (PAI-1) promotor] in a luciferase assay and observing Smad2/3 phosphorylation and their subsequent nuclear translocation.…”
Section: Introductionsupporting
confidence: 76%
“…In fact, a number of previous studies identified that altering the components of lipid rafts/caveolae may affect the TGF-β/Smad signaling pathway (30,31). In addition to SM, cholesterol is additionally a primary component of lipid rafts (30).…”
Section: Discussionmentioning
confidence: 99%
“…Cholesterol precursors and cholesterol biosimilars can regulate signal transduction and the TGF-β/Smad pathway. For example, 7-DHC (precursor) and Euphol (biosimilar) can suppress TGF-β-stimulated luciferase activity by promoting lipid raft/caveolae formation and subsequently recruiting cell-surface TGF-β receptors from non-lipid raft microdomains to lipid rafts/caveolae, where TGF-β receptors become inactive in transducing canonical signaling and undergo rapid degradation upon TGF-β binding (2931). In contrast, methyl-β-cyclodextrin, a sterol-chelating agent, reverses 7-DHC-induced suppression of TGF-β-stimulated luciferase activity by extrusion of 7-DHC from resident lipid rafts/caveolae (31).…”
Section: Discussionmentioning
confidence: 99%
“…Non-lipid raft contains small amounts of caveolin-1. This is due to the presence of mitochondria in these fractions 31 33 59 ). The *symbol indicates the slightly increased amount of TβR-II in the fraction of cells treated with PBP for 2 h as compared with that in control cells.…”
Section: Figurementioning
confidence: 96%